Analysis the Effect of Regional Original Income, Balance Funds, and Capital Expenditure on Economic Growth in Malang City - Taufiq Ismail; M Taufiq (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the influence of regional original income, balance funds, and capital expenditure on economic growth in Malang from 2006 to 2022. This research approach uses a quantitative approach. Using independent variables, namely regional original income variables, balance funds, and capital expenditures, and dependent variables are economic growth variables. Data analysis techniques use multiple linear regression analysis with the Ordinary Least Square (OLS) model with IBM SPSS 26 as a data processor. My research shows that regional real income and balance funds have a positive and significant impact on economic growth, while capital expenditure does not affect economic growth.